Reorientasi Politik Hukum Dalam Pembentukan Undang-Undang di Indonesia - Maswah, Eris Zanatul; Afrizal, Rafli; Sundawi, Sabina; Apriliani, Syifa (Media Hukum Indonesia (MHI), 2025)
Reorientation of legal politics in the formation of laws and regulations in Indonesia with a focus on the relationship between the values of Pancasila, state ideology, and legal politics that develop from time to time. As the fundamental norm of the state, Pancasila is the main guide in the formation of laws and regulations. However, reality shows that there are deviations in the direction of legal policies that tend to accommodate the ideology of liberalism and capitalism, especially in the fields of economics, politics, and natural resource management. This research uses a normative juridical approach to analyze the relationship between the legislative process, ideological values of political parties, and their impact on legal policy. The results of the study show that the formation of laws and regulations is often influenced by the political and ideological dynamics of factions in parliament, giving rise to the need to restore legal orientation to a direction that is in line with the values of Pancasila. So it must emphasize the importance of reorienting legal politics that strengthens the integrity of the Pancasila ideology in all aspects of the life of the nation and state.